TANTANGAN GURU DALAM MENGAJAR DENGAN SISTEM WORK FROM HOME PADA MASA PANDEMI COVID-19 DI MADRASAH IBTIDAIYAH - Hasan Hasan (Fakultas Studi Islam UNISKA MAB Banjarmasin, 2021)
The purpose of this study wa to determine the challenge faced by teachers in implementin pedagogic competencies during the teaching process with a work from home system. This research is located at the Madrasah Ibtidaiyah Lemo Tua, Kuajang Village, Binuang District,Polewali Mandar Regency,West Sulawesi Province.The research subjects were 6 class teachers. This research is an exploratory case study using a qualitative research approach with data analysis techniques using triangulation. The results of the study found that the challenges faced by teachers were 1) teachers had difficulties in achieving learning targets according to the curriculum, 2) teachers had difficulties in implementing online learning using technology media, 3) teachershad difficulties in assessing student learning outcomes in accordance with validation instruments and reliable data. These challenges cause teachers to be unable to maximize their pedagogical competence in teaching with a work from home system. Researchers offer ideas to answer these challenges, namely,1) the need for simplification of learning and assessment targets, 2) the need for provision of digital literacy knowledge and the use of technology for teachers, students and parents,3) the need for smartphone subsidies for teachers and students during the pandemic.